Karakterisasi Gugus Fungsi Arang Aktif Sabut Kelapa dengan Metode Pirolisis - Talubun, Anthoni; Taunaumang, Heindrich; Rampengan, Alfrie Musa (Fakultas Matematika Ilmu Pengetahuan Alam dan Kebumian, Universitas Negeri Manado, 2026)
Activated charcoal can be produced from carbon-containing materials or from activated charcoal to get a wider surface area. Coconut coir is a part of coconut waste that is rarely forgiven. The researcher discussed the functional groups of activated charcoal from coconut coir with 10 ml of KOH activator. The purpose of this study was to determine the active charcoal content contained in coconut coir. The method used is the pyrolysis method in which combustion occurs in a furnace without oxygen at a temperature of 4000C. The analysis carried out by the researchers included a wave number spectrum analysis using the FTIR tool for coconut coir activated carbon. The identification results using the FTIR spectrophotometer showed that the activated charcoal in this study contained functional groups O-H, -O-, C-O, C=C, C-H